2007
DOI: 10.1128/jvi.02706-06
|View full text |Cite
|
Sign up to set email alerts
|

Unique Thermodynamic Response of Tipranavir to Human Immunodeficiency Virus Type 1 Protease Drug Resistance Mutations

Abstract: Drug resistance is a major problem affecting the clinical efficacy of antiretroviral agents, including protease inhibitors, in the treatment of infection with human immunodeficiency virus type 1 (HIV-1)/AIDS. Consequently, the elucidation of the mechanisms by which HIV-1 protease inhibitors maintain antiviral activity in the presence of mutations is critical to the development of superior inhibitors. Tipranavir, a nonpeptidic HIV-1 protease inhibitor, has been recently approved for the treatment of HIV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 42 publications
5
118
1
1
Order By: Relevance
“…Interestingly, we found that this variant had a 7.7-fold enhanced binding affinity for ATV (K d ϭ 0.03 nM versus 0.23 nM for WT). This is in contrast to the reduced affinity reported for the mutant with the I50V single mutation (32). Thus, the I50V/A71Vdouble mutation causes a reduced affinity for APV and DRV, while rendering the protease more susceptible to ATV.…”
Section: Binding Thermodynamicscontrasting
confidence: 54%
“…Interestingly, we found that this variant had a 7.7-fold enhanced binding affinity for ATV (K d ϭ 0.03 nM versus 0.23 nM for WT). This is in contrast to the reduced affinity reported for the mutant with the I50V single mutation (32). Thus, the I50V/A71Vdouble mutation causes a reduced affinity for APV and DRV, while rendering the protease more susceptible to ATV.…”
Section: Binding Thermodynamicscontrasting
confidence: 54%
“…GRL-06579A and GRL-98065 are also potent against multidrug resistant HIV-1 strains, and molecular modeling indicates that for multidrug-resistant clinical isolates, these inhibitors maintain many of the interactions to critical active site residues (26,36). TPV, which is active against HIV-1 carrying multidrug-resistant protease, also maintains critical hydrogen bond interactions with backbone atoms in the catalytic active site of mutant protease (43).…”
Section: Discussionmentioning
confidence: 99%
“…Внедрение в клиническую практику 9 конкурентных ингибиторов протеазы ВИЧ (пВИЧ) явилось существенным прогрессом в лечении СПИДа [1,2]. Оценка энтальпии и энтропии образования молекулярных комплексов с помощью методов поверхностного плазмонного резонанса и изотермического калориметрического титрования внесли заметный вклад в разработку более эффективных конкурентных ингибиторов и их прототипов [3][4][5][6][7][8]. Однако широкое применение в клинической практике конкурентных ингибиторов пВИЧ стало приводить к появлению устойчивых вирусных штаммов [9].…”
unclassified